2013
DOI: 10.5194/hess-17-1533-2013
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation-crack-induced salinization in deep clay sediment

Abstract: Abstract.A study on water infiltration and solute transport in a clayey vadose zone underlying a dairy farm waste source was conducted to assess the impact of desiccation cracks on subsurface evaporation and salinization. The study is based on five years of continuous measurements of the temporal variation in the vadose zone water content and on the chemical and isotopic composition of the sediment and pore water in it. The isotopic composition of water stable isotopes (δ 18 O and δ 2 H) in water and sediment … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 55 publications
4
29
0
Order By: Relevance
“…2), under dry conditions, deep soil cracks are relevant for their evaporation capacity from deep parts of the soil column. Kurtzman and Scanlon (2011), Baram et al (2013) and others have reported the low water content and high salinity typical of the sediment matrix under uncultivated vertisols. Deep chloride profiles under native-land vertisols often show an increase in salinity down to 1-3 m and a relatively constant concentration in deeper parts of the vadose zone (e.g., Radford et al, 2009;Kurtzman and Scanlon, 2011;Silburn et al, 2011).…”
Section: Soil Cracks As Deep Evaporators and Unsaturated-zone Salinitymentioning
confidence: 99%
See 2 more Smart Citations
“…2), under dry conditions, deep soil cracks are relevant for their evaporation capacity from deep parts of the soil column. Kurtzman and Scanlon (2011), Baram et al (2013) and others have reported the low water content and high salinity typical of the sediment matrix under uncultivated vertisols. Deep chloride profiles under native-land vertisols often show an increase in salinity down to 1-3 m and a relatively constant concentration in deeper parts of the vadose zone (e.g., Radford et al, 2009;Kurtzman and Scanlon, 2011;Silburn et al, 2011).…”
Section: Soil Cracks As Deep Evaporators and Unsaturated-zone Salinitymentioning
confidence: 99%
“…Therefore, a dry (relatively immobile) and salty deep unsaturated matrix, developed for centuries-millennia under these non-cultivated vertisols. Nevertheless, some fresh recharge to the underlying aquifer through preferential paths related to cracks during heavy rain events creates an anomaly whereby relatively fresh water in the aquifer (e.g., ∼ 250 mg L −1 chloride; Kurtzman and Scanlon, 2011) lies beneath a salty and immobile unsaturated zone with porewater chloride concentration of a few thousands of milligrams per liter (O'Leary, 1996;Kurtzman and Scanlon, 2011;Tolmie et al, 2011;Baram et al, 2013). River, mountain-front, paleo-or other types of recharge may contribute, as well, to a situation where a relatively fresh aquifer exists under a saline vadose zone.…”
Section: Soil Cracks As Deep Evaporators and Unsaturated-zone Salinitymentioning
confidence: 99%
See 1 more Smart Citation
“…The recent development of a vadose-zone monitoring system (VMS) enables continuous monitoring of the hydrological and chemical properties of percolating water in the deep vadose zone under agriculture settings (Turkeltaub et al, 2014(Turkeltaub et al, , 2015b and other hydrological settings (e.g., Dahan et al, 2009;Baram et al, 2013). Data collected by the system comprise direct measurements of the water-percolation fluxes and the chemical evolution of the percolating water across the entire unsaturated zone.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate fate in the subsurface has been investigated by various approaches, such as (i) isotopic signature analysis in groundwater systems (Oren et al, 2004;Wassenaar et al, 2006;Showers et al, 2008;Baram et al, 2013), (ii) cropmanagement strategies, which combine crop production and nitrate leaching to the subsurface (Hanson et al, 2006;Doltra and Muñoz, 2010;Beggs et al, 2011), and (iii) studies based on data from the deep vadose zone (Dann et al, 2010;Nolan et al, 2010;Botros et al, 2012;Kurtzman et al, 2013;Dahan et al, 2014;Turkeltaub et al, 2015b). Nevertheless, estimates based on data obtained from excavated soil profiles and pore-water sampling during a short period of time represent a snapshot in time of the sediment's chemical state rather than dynamic temporal variations.…”
Section: Introductionmentioning
confidence: 99%